Peningkatan Kualitas Hidup dan Produktivitas Lansia Melalui Program Senam, Pemeriksaan dan Penyuluhan Kesehatan - Kristiono, Josafat Ago; Sushanty, Vera Rimbawani; Huroiroh, Ernawati (Jurnal Abdimas Jatibara, 2025)
This community service program has several objectives: 1) Improving the quality of the elderly's health, 2) Increasing the enthusiasm and concern of the elderly for their own health, 3) Helping the elderly to stay fit and healthy, 4) Increasing the awareness of the elderly about how to maintain their diet. by implementing a healthy menu in Padang Cermin Village. This community service activity is carried out by holding routine gymnastics for the elderly. The subjects of this program are elderly people. Implementation of activities goes through several stages, namely planning and implementing core activities. The elderly exercise program contributes to improving the health condition of the elderly, who are generally in good health without complaints of serious illness, although there are some elderly who experience health complaints.